Analysis of Hybrid Car Competitiveness in Indonesia: A Comparative Study of Toyota Hybrid and Suzuki Hybrid - Wibowo Aditya; Asyraf Naufa; Fahmi Muhammad; Wibowo Sigit (EPJ Web of Conferences)
The adoption of hybrid vehicles in Indonesia has experienced significant growth in recent years, exceeding previous market projections. Whileearlierstudiesestimatedhybridvehiclemarketsharetoremainbelow 1% without substantial policy intervention, actual sales in 2024 surpassed expectations, driven by various market and policy dynamics. This phenomenon raises the need to examine the strategic factors that influence consumer preferences in the hybrid automotive segment. This study aims to analyze the competitive positioning of leading hybrid models in Indonesia— namely the Toyota Zenix Hybrid, Suzuki Hybrid—using the Competitive Profile Matrix (CPM) approach. A survey was conducted to evaluate consumer perceptions across several Critical Success Factors (CSFs), including fuel efficiency, pricing, quality, technology, brand reputation, marketing, and after-sales service. The survey findings were then used to compare the performance of each vehicle based on consumer-assigned weights and ratings. Toyota Zenix Hybrid leads in aspects related to technical and brand strength, such as fuel efficiency, product reliability, technological innovation, and brand image. On the other hand, Suzuki’s hybrid models are perceived as more price-competitive and demonstrate slightly better performance in marketing strategy, making it appealing for value-sensitive consumers. These insights provide valuable implications for automotive manufacturers in refining their strategies and for policymakers aiming to accelerate the transition to low-emission vehicles in Indonesia.